Heart Rate Variability Predicts Cell Death and Inflammatory Responses to Global Cerebral Ischemia - Norman, Greg; Karelina, Kate; Morris, John; Zhang, Ning; Berntson, Gary; DeVries, Courtney (Frontiers in Physiology, 2012)
This study examines the relationship between autonomic functioning and neuropathology following cardiac arrest in mice. Within 24h of cardiac arrest, parasympathetic cardiac control, as indexed by heart rate variability (HRV), rapidly decreases. By day 7 after cardiac arrest, HRV is inversely correlated with neuronal damage and microglial activation in the hippocampus. Thus, by virtue of its sensitivity to central insult, HRV may offer an inexpensive, noninvasive method of monitoring neuropathological processes following cardiac arrest. The inverse linear relationships between HRV and brain damage after cardiac arrest also may partially explain why low heart rate variability is associated with increased morbidity and mortality in myocardial infarction patients.